Case report: Three cases of systemic lupus erythematosus presenting primarily with massive ascites and significantly elevated CA-125 levels and a review of pseudo-pseudo Meigs’ syndrome in literature - Li, Qiyu; Tian, Bailing (Frontiers in Immunology, 2024)
This article presents three detailed case reports and a brief review of the literature on a rare manifestation of systemic lupus erythematosus (SLE) known as Pseudo-Pseudo Meigs' Syndrome (PPMS). The patients' condition was characterized by elevated CA-125 levels, massive ascites andpleural effusion which is typically associated with ovarian malignancies but can also present in various non-malignant conditions, including SLE. A thorough literature review was conducted, summarizing similar cases and their clinical outcomes to provide a broader understanding of this uncommon syndrome. The findings emphasize the need for heightened awareness and consideration of pseudo-pseudo Meigs' syndrome in patients with SLE presenting with unexplained ascites and pleural effusion.